IMPLEMENTASI APLIKASI IKD (STUDI KASUS PELAYANAN E- KTP DI DISDUKCAPIL KOTA TANGERANG) - Iis istianah; Lita Fitriyani; Wessy Ghevira; Azmi Azra Hasan; Alivio Putra Firdaus; Irvan Ariv Kurniawan (Nusantara Hasana Journal, 2026)
The implementation of digital technology-based population administration services is one of the government's efforts to improve the quality of public services, particularly through the implementation of Digital Population Identity (IKD). This study focuses on examining the quality of population administration services through the application of IKD in supporting e-KTP services at the Population and Civil Registration Office of Tangerang City. The method used is a literature review using a descriptive qualitative approach, sourced from regulations, formal government reports, and previous related research findings. The analysis is based on Wolfinbarger and Gilly's e-service quality benchmarks, namely ease of use, website/application design, reliability, system availability and responsiveness, privacy, and empathy. The research findings show that the implementation of IKD has generally made a positive contribution to the effectiveness and efficiency of e-KTP services, particularly in reducing queues and increasing the reach of digital services. However, there are still obstacles in the form of a lack of digital literacy among the public, technical system problems, and the suboptimal dissemination of information and assistance to users. Therefore, continuous efforts are needed to improve system quality, strengthen digital education, and maximize services so that the benefits of IKD can be felt equally by all community groups.